2017
DOI: 10.3390/ijerph14080895
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Arsenic (V) from Aqueous Solutions Using Chitosan–Red Scoria and Chitosan–Pumice Blends

Abstract: In different regions across the globe, elevated arsenic contents in the groundwater constitute a major health problem. In this work, a biopolymer chitosan has been blended with volcanic rocks (red scoria and pumice) for arsenic (V) removal. The effect of three blending ratios of chitosan and volcanic rocks (1:2, 1:5 and 1:10) on arsenic removal has been studied. The optimal blending ratio was 1:5 (chitosan: volcanic rocks) with maximum adsorption capacity of 0.72 mg/g and 0.71 mg/g for chitosan: red scoria (Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 77 publications
(84 reference statements)
2
13
0
Order By: Relevance
“…In another study, banana pseudostem was used as an adsorbent for removal of Pb(II) from aqueous solution and adsorbent dose of 1 g/l was found to be optimal dose for the removal of Pb nitrate (Bagali et al 2017). Asere et al reported maximum adsorbent dose for As removal was 8 g/l (Asere et al 2017). Sumathi et al found that 1.2 g/100 ml of adsorbent dose was optimum for As removal (Sumathi and Alagumuthu 2014).…”
Section: Effect Of Adsorbent Dosementioning
confidence: 99%
“…In another study, banana pseudostem was used as an adsorbent for removal of Pb(II) from aqueous solution and adsorbent dose of 1 g/l was found to be optimal dose for the removal of Pb nitrate (Bagali et al 2017). Asere et al reported maximum adsorbent dose for As removal was 8 g/l (Asere et al 2017). Sumathi et al found that 1.2 g/100 ml of adsorbent dose was optimum for As removal (Sumathi and Alagumuthu 2014).…”
Section: Effect Of Adsorbent Dosementioning
confidence: 99%
“…[ 28 , 29 ]. Although several studies have been conducted on the application of volcanic rocks for pollutants-laden wastewaters [ 28 , 29 , 30 , 31 ], very little research has been directed to the defluoridation of groundwater using volcanic rocks.…”
Section: Introductionmentioning
confidence: 99%
“…Pumice is among the most promising volcanic rocks studied as low-cost adsorbents mainly for heavy metals. [27][28][29][30][31] It has a more comprehensive global distribution in areas with young volcanic fields, including the East Africa countries such as Ethiopia, Eritrea, Kenya, and Tanzania. 32 The Ethiopia Rift, which covers around 30% of the area of the country, is rich in pumice.…”
Section: Introductionmentioning
confidence: 99%